Influence Of Planting Methods And Density On Growth, Development And Yield Of Early Potatoes. (Texas Journal of Agriculture and Biological Sciences, 2022)
This article presents data on the cultivation of early potato varieties "Condor" and "Sante" in the open field using resource-saving innovative technologies for the cultivation of early varieties. Ultimately, when sowing potatoes in the open field, it was found that when cultivating early sowing varieties of Condor and Sante, data were obtained on growth, development, yield, protection from pests and the collection of early potatoes.